Oceanic Explorations Lapita and Western Pacific Settlement - Bedford, Stuart; Sand, Christophe; Connaughton, Sean P. (Terra Australis, 2007)
Lapita comprises an archaeological horizon that is fundamental to the understanding of human colonisation and settlement of the Pacific as it is associated with the arrival of the common ancestors of the Polynesians and many Austronesian-speaking Melanesians more than 3000 years ago. While Lapita archaeology has captured the imagination and sustained the focus of archaeologists for more than 50 years, more recent discoveries have inspired renewed interpretations and assessments. Oceanic Explorations reports on a number of these latest discoveries and includes papers which reassess the Lapita phenomenon in light of this new data. They reflect on a broad range of interrelated themes including Lapita chronology, patterns of settlement, migration, interaction and exchange, ritual behaviour, sampling strategies and ceramic analyses, all of which relate to aspects highlighting both advances and continuing impediments associated with Lapita research.